Conceptual Framework on Market Orientation and Performance of SMEs: Alliances as Mediating - Maluwis Maratis; Jaratin Lily; Chew Tze Cheng @ Nur Alesha Chew; Rini Suryati Sulong (Penerbit UMS, 2023)
Firm capabilities become important to SMEs' performance in expanding to foreign markets. Many countries focus on helping these SMEs because of the rapid internalization of competitors. This paper aims to propose a conceptual framework by identifying the determining factor that affects the international performance of Malaysian SMEs. Two capabilities that have determined the international performance of SMEs are market orientation and alliances. This framework was developed based on an extensive literature review. According to the proposed framework, alliances mediate the relationship between market orientation and international performance. Few studies have attempted to investigate the market orientation on international performance with mediating effect of alliances on international performance, especially in developing countries. This paper suggests that future researchers need to pay extra attention to the international performance of SMEs in emerging markets, including Malaysia.